Une politique du « vivre avec » un fleuve et ses débordements - Audrey Richard-Ferroudji; Nadia Dupont; Séverine Durand; Frédéric Grelot (VertigO)
The expression "living with" flooding is present today in various planning documents. What policy does it promote ? How is it translated into actions ? From the case of the Orb delta (Hérault, France) and especially the Faubourg quarter in Beziers, this article discusses the shape of a policy of "living with". Several methods of inquiry were implemented to vary situations of wording flood: interviews, focus groups, observations and questionnaire. We identify five logics of management and discuss typical actions of this policy. This case enlightens a management of floods based on ways of living in an area.